2017
DOI: 10.1101/196063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive deficits and increases in creatine precursors in a brain-specific knockout of the creatine transporter geneSlc6a8

Abstract: (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint . http://dx.doi.org/10.1101/196063 doi: bioRxiv preprint first posted online Sep. 29, 2017; 2 AbstractCreatine transporter (CrT; SLC6A8) deficiency (CTD) is an X-linked disorder characterized by severe cognitive deficits, impairments in language, and an absence of brain creatine (Cr). In a previous study, we generated floxed Slc6a8 (Slc6a8 flox ) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…20 Female heterozygous 23 and brain-specific knockouts were hyperactive. 21 While P5KO mice were hyperactive during the dark phase compared with the WT-VEH mice, this was likely due to tamoxifen administration since all mice treated with tamoxifen from P5 to 10 were hyperactive. To our knowledge this is the first study that has shown that neonatal tamoxifen exposure leads to nocturnal hyperactivity.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…20 Female heterozygous 23 and brain-specific knockouts were hyperactive. 21 While P5KO mice were hyperactive during the dark phase compared with the WT-VEH mice, this was likely due to tamoxifen administration since all mice treated with tamoxifen from P5 to 10 were hyperactive. To our knowledge this is the first study that has shown that neonatal tamoxifen exposure leads to nocturnal hyperactivity.…”
Section: Discussionmentioning
confidence: 95%
“…However, mice with a brain-specific Slc6a8 deletion show visible platform deficits and do not have weight differences. 21 In addition, the P5KO mice do show improvement over trials, suggesting that they are able to perform and learn the task. Finally, the P5KO mice do not show swim speed deficits during the hidden platform trials suggesting that the loss of Cr does not directly impact physical performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that Slc6a8 -/y and Slc6a8 +/mice have cognitive deficits that are caused by the lack of brain Cr (Skelton et al 2011;Udobi et al 2018). It is important to determine what other behaviors may be disrupted by the lack of Cr.…”
Section: Discussionmentioning
confidence: 99%